Luciana Littizzetto, il postfemminismo e la rischiosa arte di fare la scema - Bonifazio, Paola (Incontri. Rivista europea di studi italiani, 2014)
Luciana Littizzetto, postfeminism, and the dangerous art of playing the foolThe goal of this paper is to study the performative strategies by which the comic persona of Luciana Littizzetto deconstructs post-patriarchal representations of femininity and womanhood in contemporary Italian popular culture. I argue that Littizzetto’s character(s) (on television and in films) engages in a ‘postfeminist’ critique of the system of sex and power, in which many women have recently found their fortune, and that is primarily embodied by the showgirls and/or female politicians supported by the ex-Prime Minister Silvio Berlusconi. By positioning herself as the woman who is excluded from the circle of power to which other (beautiful and attractive) women have access, Littizzetto’s character(s) unveils the contradictions that embed ‘postfeminist’ models of female emancipation, blessed (or cursed) by the archaic power of beauty, as well as empowered by sexual liberation. I will purposefully use the attribute ‘postfeminist’ to describe both the comic subject and the female ‘White Clowns’ in Littizzetto’s comic performance. In this way, I hope to highlight the complexity of the attribute itself, rather than using the term as a fixed category of analysis. In my view, ‘postfeminism’ indicates both continuities between contemporary practices of female emancipation and second wave feminism, as well as a dismissal. In my essay, I will show that Littizzetto’s comic act does not aim at denigrating the ‘other’ woman and lacks the underlining moralistic attitude of other critical voices, such as Lorella Zanardo and her Il corpo delle donne. Rather, it is crafted against a ‘queen’ whose power is not denied but rather acknowledged and therefore naked. By physical gestures and verbal expressions, her living and acting persona ultimately exposes the masquerade of femininity, both her own and that of others.